A quantitative in-depth analysis of the prototype sdB+BD system SDSS J08205+0008 revisited in the Gaia era. Issue 3 (25th November 2020) - Schaffenroth, V; Casewell, S L; Schneider, D; Kilkenny, D; Geier, S; Heber, U; Irrgang, A; Przybilla, N; Marsh, T R; Littlefair, S P; Dhillon, V S
ABSTRACT: Subdwarf B stars are core-helium-burning stars located on the extreme horizontal branch (EHB). Extensive mass loss on the red giant branch is necessary to form them. It has been proposed that substellar companions could lead to the required mass loss when they are engulfed in the envelope of the red giant star. J08205+0008 was the first example of a hot subdwarf star with a close, substellar companion candidate to be found. Here, we perform an in-depth re-analysis of this important system with much higher quality data allowing additional analysis methods. From the higher resolution spectra obtained with ESO-VLT/XSHOOTER, we derive the chemical abundances of the hot subdwarf as well as its rotational velocity. Using the Gaia parallax and a fit to the spectral energy distribution in the secondary eclipse, tight constraints to the radius of the hot subdwarf are derived. From a long-term photometric campaign, we detected a significant period decrease of $-3.2(8)× 10^{-12} \, \rm dd^{-1}$ . This can be explained by the non-synchronized hot subdwarf star being spun up by tidal interactions forcing it to become synchronized. From the rate of period decrease we could derive the synchronization time-scale to be 4 Myr, much smaller than the lifetime on EHB. By combining all different methods, we could constrain the hot subdwarf to a mass of $0.39\!-\!0.50\, \rm M_\odot$ and a radius of $R_{\rm sdB}=0.194± 0.008\, \rm R_\odot$, and the companion to $0.061\!-\!0.071\rm \, M_\odot$ with a radius of $R_{\rm comp}=0.092 ± 0.005\, \rm R_\odot$, below the hydrogen-burning limit. We therefore confirm that the companion is most likely a massive brown dwarf.